Taste Dysfunction in COVID-19 Patients; A Cross-Sectional Observational Study - Sreedevi Nunkappa Thippeswamy; Keerthi Kumar Kabbyar Chidananda; Kamalesh Tagadur Nataraju (Bengal Journal of Otolaryngology and Head Neck Surgery, 2023)
Introduction:It has been observed that olfactory dysfunction (anosmia, hyposmia and parosmia) and gustatory (taste) dysfunction (ageusia, hypogeusia and dysgeusia) are one of the classical presentations of COVID-19. Gustatory (taste) dysfunction attributable partly to loss of retro-nasal olfaction (which adds to the flavour, a component of taste sensation) while eating or drinking food.